Influence of Heparin and a Low Molecular Weight Heparinoid on Specific Endogenous and Exogenous Fibrinolytic Factors during Rest and Exercise - de Boer, A; Kluft, C; Dooijewaard, G; Kasper, F J; Kroon, J M; Breimer, D D; Stiekema, J C J; Cohen, A F (Thrombosis and Haemostasis, 1992)
The effects of heparin (5,000 IU i.v.) and the low molecular weight heparinoid Org 10172 (Orgaran®) (3,250 anti-Xa units i. v.) on components of the fibrinolytic system were studied in two double-blind, randomised, placebo-controlled, cross-over trials using healthy subjects. In study A (n = 6) the effects were studied during rest and standardized exercise and in study B (n = 6) during a low dose infusion of recombinant tissue-type plasminogen activator (rt-PA; 80 µg over 16 min). At rest, heparin and Org 10172 did not influence the plasma concentrations of endogenous t-PA antigen, and activity, urokinase-type PA (u-PA) antigen, plasmin activatable pro-urokinase (scu-PA), active urokinase (tcu-PA) and plasminogen activator inhibitor-1 (PAI-1) antigen. Recombinant t-PA antigen and activity during rt-PA infusion were also not affected. During exercise, neither heparin nor Org 10172 influenced the area under the curve (AUC) of t-PA and u-PA antigen and t-PA activity when compared with placebo. Unexpectedly, after heparin the AUC of t-PA activity was 49% larger (range +19 to +245%) than after Org 10172 (p <0.05). The last difference was considered spurious. scu-PA, tcu-PA and PAI-1 antigen levels at 2 min after termination of exercise were unaffected by both compounds (p >0.05). Sulphated polysaccharides do not increase fibrinolytic activity of the plasma by changing the concentrations of the components of the fibrinolytic system.